How time-use and transportation barriers limit on-campus participation of university students. (October 2018) - Allen, Jeff; Farber, Steven
Highlights: Analysis of a 1-day travel survey of students in the Greater Toronto Area. Derivation and descriptive analysis of transportation network variables. Modelling the affects of whether students feel commuting dissuades participation. Modelling how transport and time-use factors affect weekly commute rates. Abstract: Success in postsecondary education is related to the amount of time spent on campus. The more often students attend class and access on-campus learning resources, the better their grades and the lower their dropout rates. Despite the importance of on-campus participation in student outcomes, some students living in large cities face tremendous transportation and time-use barriers that make it difficult to spend more time on campus. Accordingly, the objective of this paper is to examine the mobility factors that prevent students from attending their campuses in the Greater Toronto Area (GTA). Specifically, we examine student disparities in barriers to participate based on where they live, their mobility options, as well as the time constraints of their daily activity patterns (e.g. part time work). Data is drawn from a 1-day travel survey of students across seven university campuses in the GTA. This is augmented with computationally derived transport accessibility factors. Multivariate logistic regression models are then employed to uncover the mobility-related determinants for a) if students feel commuting discourages them from travelling to campus; b) if students pick courses based on their commute; c) if commuting discourages students from participating in university organized activities; and d) how many days per week a student visits campus. The results of these models fuel a discussion of how to limit mobility-related barriers to postsecondary student participation.